Transfer Of Rural Funds Through Branches Of Commercial Banks: A Note (Bangladesh Journal of Public Administration, 2021)
The major thrust of the present paper is to find relevance in Banglades11 of the thesis developed by ~~rdal' with regard to the flow of transfer of funds from less developed areas to the more developed ones. This process is termed by him as "backwash effects." The logic of such fund transfer, as shown by him, lies in the possibility of getting relatively higher return from investing funds in the more developed areas. It may be noted here that the present study is limited to the rural operations of commercial banks in Bangladesh. Comnlercial Banks are szlected for this purpose mainly because the same appears to be relatively more prominent2 in terms of the volume of transactions compared to other agencies operating in the rural financial market of Bangladesh.